Testbeds and research infrastructures. Development of networks and communities 6th international ICST conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, revised selected papers - Gavras, Anastasius; Thanh, Nguyen Huu; Chase, Jeffry S. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2011)
This book constitutes the proceedings of the 6th International ICST Conference, TridentCom 2010, held in Berlin, Germany, in May 2010. Out of more than 100 submitted contributions the Program Committee finally selected 15 full papers, 26 practices papers, and 22 posters. They focus on topics as Internet testbeds, future Internet research, wireless sensors, media and mobility, and monitoring in large scale testbeds.